Sol Concentration Effects on Sol-Gel Spin Coated Indium Nitride Thin Films - Zhi, Yin Lee; Sha, Shiong Ng; Fong, Kwong Yam (2016)
Indium nitride (InN) is a potential semiconductor material in the development of optical and electronic devices due to its unique properties such as the narrow ene1·gy band gap of 0.7 - 1.0 eV, high electron mobility and low carrier concentration. The present work focu sses on the synthesis of InN thin films using sol-gel spin coating method. It is relatively simple. Fast processing and cost effective in producing thin films as compared to the conventional deposition methods such as mol ecular beam epitaxy, metal-organic chemical vapour deposition and reactive sputtering which inv oll'c the ultrahi gh vacuum system , complicated and expensive setup. In this experiment, precursor with different sol concentrations of 0.05 and 0.10 M were prepared. The sol concentration effects on the structural properties and surface morphologies of the deposited thin films were investigated. In addition, the cross-sectional analysis was perlom1ed to determine the resulting film thickness. X-ray diffi·action measurements show that the lnN thin film with better crystalline quality can be obtained at sol concentration of 0.05 M. Field emission scanning c·ku 1on minosco py im ages reveal that the InN thin film prepared using sol 0.05 M exhibits surface with closely packed InN grains; while that prepared using sol 0.10 M exhibits surface with tiny cracks. In this study, it can be concluded at the 0.05 M is the optimal sol concentration for the synthesis of lnN.